Pengembangan Modul Bimbingan Kelompok dengan Teknik Role Playing untuk Meningkatkan Kepercayaan Diri Siswa - Sulandari, Sisca; Rochani, Rochani; Handoyo, Alfiandy Warih (Peneliti.net, 2025)
This research is motivated by the issue of a lack of self-confidence often experienced by teenagers in educational institutions, especially high school students, including those at SMA Negeri 19 Tangerang Regency. One effort to increase students' self-confidence is by providing group counseling services using the Role Playing technique. This study aims to develop a group counseling module with the Role Playing technique, which is expected to enhance students' self-confidence. The method used by the researcher is the research and development (R&D) method, utilizing the 4D development stages: define, design, development, and dissemination. The results of the feasibility test on the research product yielded an average score of 92.7%, categorized as